2018
DOI: 10.1515/htmp-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Temperature Oxidation on Hydrogen Absorption and Degradation of Zircaloy-2 and Zr 700 Alloys

Abstract: The present research was aimed at determining the effects of the oxide layers on hydrogen absorption, microstructure and mechanical properties of the Zircaloy-2 and Zr 702 alloys. The oxidation was made at 350 °C, 700 °C and 900 °C for 10 to 30 min in laboratory air, followed by hydrogen cathodic charging for 72 h and annealing at 400 °C for 4 h. The slow strain rate tests were carried out on oxidized, charged and annealed specimens. The oxidation resulted in thick and cracked, more for Zr 702 alloy, layer. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…The applied cathodic charging has been already used several times [22][23][24][25][26] and may result in the hydrogenation of Zr alloys even at room temperature after further annealing. The hydrogen content in these tests was not measured, but it should be close to the values given for similar alloys in our earlier research [27]. Such hydrogen content is certainly above the limit hydrogen solubility value at room temperature.…”
Section: Effect Of Oxide Layer On Hydrogen Absorption and Degradationsupporting
confidence: 86%
“…The applied cathodic charging has been already used several times [22][23][24][25][26] and may result in the hydrogenation of Zr alloys even at room temperature after further annealing. The hydrogen content in these tests was not measured, but it should be close to the values given for similar alloys in our earlier research [27]. Such hydrogen content is certainly above the limit hydrogen solubility value at room temperature.…”
Section: Effect Of Oxide Layer On Hydrogen Absorption and Degradationsupporting
confidence: 86%
“…Every specimen in this study possessed the crack or multiple cracks on the top of a bulge. The descaling, again much more intensive on the outer surface, is an obvious consequence of developing cracking as already observed [29].…”
Section: Oxidation At 1273 Ksupporting
confidence: 68%
“…The oxide layers possess small columnar grains and equiaxed grains [4]. The cracking of oxide layers at relatively low oxidation temperature was often observed [29,30]. The cracking of the oxide layer was explained by the accumulation of compressive stresses in the oxide at the interface in pre-transition stage, resulting from imperfect accommodation of the volume expansion attendant upon oxide formation [2].…”
Section: Oxidation At 1273 Kmentioning
confidence: 99%
“…The width of the oxide layer was the largest near the cracks. The previously performed monitoring of oxidation time [60] showed that after oxidation at 900 • C, the cracks appeared on the surface already after 20 min of oxidation and were relatively long, even up to 35 µm. The oxide layer was substantially thicker in this area.…”
Section: Methodsmentioning
confidence: 95%
“…Despite this knowledge, the influence of the oxide layer characteristics on hydrogen absorption was not often investigated. The applied cathodic charging in cold or heated electrolytes was already utilized [14,20,38,50,56,57,60,[84][85][86][87], resulting in the appearance of hydrogen within a thin subsurface layer, mainly as the hydrides and saturated or oversaturated hydrogen interstitial solution. The further annealing (here called homogenizing heat treatment) resulted in a uniform hydrogen concentration.…”
Section: Barrier Effect Of the Oxide Layermentioning
confidence: 99%